Prevalence of communication disorders among school children in Ballari, South India: A cross-sectional study - Sunil Kumar Ravi; P. Sumanth; T. Saraswathi; Mohammed Asif Basha Chinoor; N. Ashwini; Ejaz Ahemed (Elsevier, 2021)
Introduction: Congenital or acquired childhood communication disorders can negatively impact the emotional, social and academic skills in children. Research studies have reported that school going children are at higher risk of having communication disorders which will affect their academic and other skills. However, there is a dearth of studies on epidemiological data on communication disorders in school going children hence the present study was carried out to estimate the prevalence of communication disorders among school going children of Ballari district. Method: In a Cross-sectional study carried out on 2304 school going children (6-16years) of primary and secondary government schools in rural areas of Ballari district, Karnataka were screened using subjective & objective measures for communication disorders. Results: The results revealed a total of 99 out of 2304 children were identified with communication disorders indicating a prevalence rate of 4.29%. Among them, a total of 75 children were having hearing and otological disorders (3.25%) and 24 children were having speech and language disorders (1.04%). Further, the prevalence of communication disorders was found to be higher among males (2.38%) compared to females (1.91%). Conclusion: The present study found a lesser prevalence rate of communication disorder in school aged children of Ballari district, than the previous studies. Hearing loss and otological problems such as impacted cerumen, ear pain, ear discharge, etc., were found to be more than speech-language disorders such as stuttering, speech sound disorders and child language disorders.